Ethanol modified supercritical carbon dioxide extraction of antioxidant rich extract from Pereskia bleo - Sharif, K. M.; Rahman, Md. Mokhlesur; Azmir, Jannatul; Shamsudin, Siti Hadijah; Uddin, Md. Sayed; Fahim, T. K.; Sarker, Md. Zaidul Islam (The Korean Society of Industrial and Engineering Chemistry., 2015)
Supercritical fluid extraction (SFE) of Pereskia bleo leaves was carried out with systematic experimental study to screen and optimize the factors affecting yield and antioxidant activity. Initially, five factors were studied by Plackett–Burman study to screen the most influential factors. Consequently, three significantly affecting factors were optimized by Box–Behnken study. At the optimum condition (52 °C, 36 MPa and 1.5% ethanol of total CO2) yield and IC50 value obtained by SFE were higher than water extract and lower than methanol extract. GC–MS analysis showed that the ethanol modified supercritical carbon dioxide has increased efficiency for extracting antioxidant compounds, α-tocopherol, β-sitosterol and erythritol.